2017
DOI: 10.1002/2017gl075283
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Energy From MgO Exsolution to Power Early Geodynamo

Abstract: The origin of Earth's ancient magnetic field is an outstanding problem. It has recently been proposed that exsolution of MgO from the core may provide sufficient energy to drive an early geodynamo. Here we present new experiments on Mg partitioning between iron‐rich liquids and silicate/oxide melts. Our results indicate that Mg partitioning depends strongly on the oxygen content in the iron‐rich liquid, in contrast to previous findings that it depends only on temperature. Consequently, MgO exsolution during co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
53
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 28 publications
14
53
2
Order By: Relevance
“…Our results confirm the previous findings that K Mg strongly depends on X o, oxygen concentration in the Fe alloy (Du et al, ), evident from Figure b as discussed above. Du et al () did not constrain the temperature dependence of K Mg due to limited data set. Our new results provide important constraints: moderate temperature and pressure control on K Mg , namely, small b and c , for 1/ T and P / T terms, respectively.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results confirm the previous findings that K Mg strongly depends on X o, oxygen concentration in the Fe alloy (Du et al, ), evident from Figure b as discussed above. Du et al () did not constrain the temperature dependence of K Mg due to limited data set. Our new results provide important constraints: moderate temperature and pressure control on K Mg , namely, small b and c , for 1/ T and P / T terms, respectively.…”
Section: Resultssupporting
confidence: 93%
“…So sulfur does not directly influence Mg partitioning, in agreement with our regression result, where parameter g is statistically insignificant. In our study, Mg content is below detection limit in S‐poor Fe alloy, primarily due to its low oxygen contents, in agreement with previous findings (Badro et al, ; Du et al, ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…But those same experiments (e.g., Badro et al, 2016Badro et al, , 2018Blanchard et al, 2017;Bouhifd & Jephcoat, 2011;Chidester et al, 2017;Du et al, 2017;Fischer et al, 2015;Huang & Badro, 2018;Jackson et al, 2018;Ricolleau et al, 2011;Siebert et al, 2012Siebert et al, , 2013Tsuno et al, 2013) have not observed any SiO 2 exsolution and even support that the present-day core could be undersaturated in Si and O (Brodholt & Badro, 2017). But those same experiments (e.g., Badro et al, 2016Badro et al, , 2018Blanchard et al, 2017;Bouhifd & Jephcoat, 2011;Chidester et al, 2017;Du et al, 2017;Fischer et al, 2015;Huang & Badro, 2018;Jackson et al, 2018;Ricolleau et al, 2011;Siebert et al, 2012Siebert et al, , 2013Tsuno et al, 2013) have not observed any SiO 2 exsolution and even support that the present-day core could be undersaturated in Si and O (Brodholt & Badro, 2017).…”
Section: /2019gl082722mentioning
confidence: 88%